Metalloporphyrin anion sensors: the effect of the metal centre on the anion binding properties of amide-functionalised and tetraphenyl metalloporphyrins. - Cormode, D; Drew, MG; Jagessar, R; Beer, P (2008)
This article describes the synthesis and anion binding properties of a series of 'picket fence' metalloporphyrin complexes, within which the metal centre is systematically varied. The porphyrin structure contains four amide bonds and is the same for each metal. The anion binding properties of these receptors are further contrasted with those of their tetraphenylporphyrin congeners to elucidate both the effect of the metal centre and the influence of the amide groups on the anion recognition process. Anion binding was demonstrated using UV/visible and (1)H NMR spectroscopies, electrochemistry and luminescence. The metal centre was found to be highly influential in the strength and selectivity of binding; for example, the cadmium and mercury complexes exhibited far greater affinities for anions than the zinc complexes in competitive solvents such as DMSO. The amide functionalities were found to enhance the anion binding process.